Volt-VAR multiobjective optimization to peak-load relief and energy efficiency in distribution networks - Padilha-Feltrin, Antonio [UNESP]; Quijano Rodezno, Darwin Alexis [UNESP]; Sanches Mantovani, José Roberto [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2015)
This paper addresses the integrated volt-var control for distribution network operation via multiobjective optimization. This paper seeks to explore the problem of energy savings and peak demand relief through the voltage reduction procedure. Currently, due to the emergence of the distribution smart grids, these procedures are gaining renewed interest and attention. The proposal presented here is for the operation phase, with a strategy based on an hourly load forecast for the next day/week, taking into account the active power intake reduction, and the voltage deviation. Therefore, the result is a set of nondominated optimal solutions, and then one may decide when, where, and how to apply them to meet different goals. The obtained solutions, for two typical distribution networks, describe relevant economic and technical benefits.
Keywords: Distribution systems; Integrated volt-var control; Multiobjective optimization; Voltage reduction